A formação pedagógica do professor para a docência na educação superior: área de administração - Dias, Edna Maria Leite (2017)
One of the current concerns related to the pedagogic training of teachers, debated nationally and internationally, is the institutionalization of programs, projects or isolated activities of formation guided by specific laws of each country, which should be promulgated by education entities, such as: Ministries, Councils and Secretaries. The discussion about pedagogic formation of teachers to practice teaching in higher education was intensified after 90ies in Spain, Portugal and Brazil, countries which had the most profound theoretical-practical discussions to organize the proposal of pedagogic formation of teachers. In Brazil, specifically, the reduced legislation on the training in question referred to in the LDB is art. 66, which provoked in the HEI of the country the importance of organizing this training in isolated programs, projects or actions defined within the framework of HEIs with internal evaluation. Many experiences has already been planned and developed in Brazil. In the context presented and due to our experience in pedagogical management in a private HEI located in Fortaleza – CE, that emerged the motivation to investigate how formation discussed was developed at the area of Administration in two HEI in Fortaleza-CE. The main point of investigation was: “Is the pedagogic formation of teachers to exercise teaching at Administration in private HEI‟s institutionalized, integrating pedagogic dimension and specific dimensions of knowledge at Administration‟s area? Based on the this point, we systematized: Pedagogic formation to teaching in higher education is a determinant point to teaching performance and must be institutionalized in private HEI, integrating pedagogic dimension to the dimensions of specific knowledge of Administration. The method of qualitative approach and the strategy performed at the research was exploratory and descriptive. We performed the thematic analysis described by Bardin (2011), for secondary data.The thesis waspartially confirmed, the objectives were achieved and we identified that teaching pedagogic formation programs offered by the researched HEIs are systematized and with regular frequency of teacher training, integrating the pedagogical dimension with the specific knowledge dimensions in the area of administration, still in the structuring phase..